High-Context vs. Low-Context Communication in English: A Cross-Cultural Study of Indonesian and American Interaction in Puri Viera’s Instagram Reels - Weny, Krisna; Rahmah, Cut Nadia Muji; Lubis, Aisyah Inka Putri; Perangin-angin, Alemina Br.; Lestari, Dwi Putri (Linguistics and ELT Journal, 2025)
This study explores the manifestations of high-context and low-context communication styles within cross-cultural interactions between Indonesian and American speakers, as portrayed in Puri Viera’s Instagram Reels as the lack of studies by using Indonesian and American as the participants. Utilizing Edward T. Hall’s theory of context communication, the research employs a qualitative content analysis approach to identify and analyze verbal and non-verbal communication patterns. The analysis reveals distinct cultural markers: Indonesian speakers tend to favor indirectness, contextual reliance, and nonverbal cues (high-context), while American speakers exhibit directness, explicitness, and linear logic (low-context). These distinctions not only underscore cultural communication preferences but also demonstrate how digital platforms like Instagram facilitate intercultural dialogue. The findings contribute to the broader understanding of intercultural communication dynamics in digital spaces and provide practical implications for fostering effective, culturally aware interactions on social media.